Giant Congenital Melanocytic Nevi (GCMN): Sebuah Laporan Kasus Langka - Erico Lemuel Yonathan; Hari Darmawan (Universitas Wijaya Kusuma Surabaya, 2021)
Giant Congenital Melanocytic Nevi (GCMN) is a nevus which present at birth or arise within the first few weeks of life. Incidence of GCMN is estimated at below 1:20.000 newborns. Lesion of GCMN usually appears with a black or brownish plaque and may have abnormal borders, flat or protruding surface and hypertrichosis. Giant Congenital Melanocytic Nevi (GCMN) is associated with malignant melanoma and neurocutaneous melanocytosis. A male newborn baby is reported to have a giant black hairy plaque, with irregular shape in his head since born. Patient was born naturally, full term, and normal birth weight. The mother has no medication consumption and disease history during pregnancy. In our three years follow up, there are multiple black patches with smaller size in front right and left leg, and the back of the body. The GCMN treatment consists of surgical and non-surgical procedures, psychological support, and lifelong monitoring. In this case, further examination and observation are needed.